Antarctic ice shelf response to ocean tides and atmospheric pressure variations using satellite interferometry - Odh, Anna (UiT The Arctic University of Norway, 2024)
Ice shelves, the floating extensions of the Antarctic ice sheet, are supporting the upstream ice and regulates the outflow into the ocean. They are a key component in future predictions of sea level rise, as their direct contact with both the ocean and the atmosphere makes them subject to changing climatic conditions. This thesis aims to investigate how Fimbulisen, a large ice shelf in East Antarctica, responds to oceanic and atmospheric forcing through the use of satellite images in addition to tidal- and atmospheric pressure model data. As ice shelves float on the ocean, processes that make the sea level fluctuate, like oceanic tides and variations in atmospheric pressure, will affect their vertical movements. The vertical movement of an ice shelf can be analysed on the cm-scale with a satellite remote sensing technique called Triple- and Quadruple differential interferometry (T/Q-DInSAR). The T/Q-DInSAR imagery used in this thesis is derived from large swath (400 km) Synthetic Aperture Radar (SAR) imagery, covering the whole ice shelf of Fimbulisen. In addition, an Antarctic regional tide model, CATS2008a, and a global atmospheric pressure model, ECMWF ERA5 reanalysis, are used in this thesis. Output from these models is processed to fit the interferometric epochs, shape and extent of the T/Q-DInSAR images, and subsequently, their effects on vertical movement are subtracted from the T/Q-DInSAR images. The remaining effects after subtraction, are assumed to tie to either inaccuracies in the tide- or atmospheric pressure models, or to other significant geophysical processes affecting the vertical movement of Fimbulisen. The results show that the combination of the two models can resolve vertical movement adequately in well-known, freely floating cavities of ice shelves. The models do not resolve areas with ice rises and rumples well, probably due to ice flexure not being captured by the models. Trolltunga, a part of Fimbulisen overhanging the continental shelf break, is exposed to the Southern Ocean and ...